2020
DOI: 10.1098/rsob.200252
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of olfactory detection in insects: beyond receptors

Abstract: Insects thrive in diverse ecological niches in large part because of their highly sophisticated olfactory systems. Over the last two decades, a major focus in the study of insect olfaction has been on the role of olfactory receptors in mediating neuronal responses to environmental chemicals. In vivo , these receptors operate in specialized structures, called sensilla, which comprise neurons and non-neuronal support cells, extracellular lymph fluid and a precisely shaped cuticle. While s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 157 publications
(264 reference statements)
0
81
0
1
Order By: Relevance
“…It is found useful in providing insights into the relationship between OSN anatomy and olfactory physiology [ 83 , 84 ]. A recent review of these new molecular tools and mechanisms of olfactory detection in insects has been published [ 85 ].…”
Section: Mechanisms Of Insect Sex Pheromone Perceptionmentioning
confidence: 99%
“…It is found useful in providing insights into the relationship between OSN anatomy and olfactory physiology [ 83 , 84 ]. A recent review of these new molecular tools and mechanisms of olfactory detection in insects has been published [ 85 ].…”
Section: Mechanisms Of Insect Sex Pheromone Perceptionmentioning
confidence: 99%
“…The invertebrate phototransduction cascade has also been reviewed extensively (Hardie, 2012 ; Montell, 2012 ; Hardie and Juusola, 2015 ), while olfactory transduction is still under active investigation (Touhara and Vosshall, 2009 ; Schmidt and Benton, 2020 ). In this review we will focus on Drosophila olfactory and visual transduction for simplicity, however several studies have identified many differences between invertebrate species including different receptors and transduction signaling mechanisms (for recent reviews, see Honkanen et al, 2017 ; Schmidt and Benton, 2020 ). The main steps of the transduction are shown in Figures 4 , 5 , and described below, with the main components listed in Table 1 for comparison.…”
Section: Invertebrate Sensory Transduction Cascadesmentioning
confidence: 99%
“…Invertebrate olfactory transduction appears to use a diverse set of pathways across species, within a single species, and even within a single OSN (for a recent review, see Schmidt and Benton, 2020 ). The receptors can be divided into two different classes; (1) seven transmembrane domain odorant receptors (ORs) (Clyne et al, 1999 ) and (2) three transmembrane domain ionotropic receptors (IRs, see Table 1 ; Benton et al, 2009 ).…”
Section: Invertebrate Sensory Transduction Cascadesmentioning
confidence: 99%
See 1 more Smart Citation
“…pheromone) to the environment that provokes a physiological and/or behavioral reaction in the receiver 11 . So far, most research on chemical communication has been done in insects, for which the chemical nature of specific molecules and their mechanism of action is known to some extent 12 , 13 . Although many vertebrates are adept at detecting odoriferous stimuli, much less research has been done in this group compared to insects 13 .…”
Section: Introductionmentioning
confidence: 99%